2017
DOI: 10.1038/ncomms14418
|View full text |Cite
|
Sign up to set email alerts
|

The non-coding variant rs1800734 enhances DCLK3 expression through long-range interaction and promotes colorectal cancer progression

Abstract: Genome-wide association studies have identified a great number of non-coding risk variants for colorectal cancer (CRC). To date, the majority of these variants have not been functionally studied. Identification of allele-specific transcription factor (TF) binding is of great importance to understand regulatory consequences of such variants. A recently developed proteome-wide analysis of disease-associated SNPs (PWAS) enables identification of TF-DNA interactions in an unbiased manner. Here we perform a large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 67 publications
0
50
0
Order By: Relevance
“…Previous studies have proven that AP4 could be a positive or negative regulator of tumour‐related genes by binding the E‐box of their promoters (Jackstadt et al ., ; Liu et al ., ). Here, we demonstrated that AP4 could bind within the LAPTM4B polymorphism region in vitro and in vivo and function as a positive transcriptional regulator.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proven that AP4 could be a positive or negative regulator of tumour‐related genes by binding the E‐box of their promoters (Jackstadt et al ., ; Liu et al ., ). Here, we demonstrated that AP4 could bind within the LAPTM4B polymorphism region in vitro and in vivo and function as a positive transcriptional regulator.…”
Section: Discussionmentioning
confidence: 99%
“…The high‐throughput chromosome conformation capture (Hi‐C) technique can be used to analyze the overall spatial conformation of chromosomes and investigate their physical properties at high resolution . It has been reported that the noncoding variants might affect distal target genes via long‐range loop formation . To validate the long‐range regulation between prioritized SNPs and RANKL , we downloaded Hi‐C or capture Hi‐C data on GM12878 and CD34 + cells from several studies, to query whether those genetics variants and RANKL were within the same chromatin interaction.…”
Section: Methodsmentioning
confidence: 99%
“…(34,35) It has been reported that the noncoding variants might affect distal target genes via long-range loop formation. (23,36) To validate the long-range regulation between prioritized SNPs and RANKL, we downloaded Hi-C or capture Hi-C data on GM12878 and CD34 þ cells from several studies, (37,38) to query whether those genetics variants and RANKL were within the same chromatin interaction. Topologically associating domains (TADs) are chromosomal regions within which DNA sequences most often establish long-range physical contact.…”
Section: Cis-expression Quantitative Trait Locus Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR plate has been utilized for genomic studies [29, 30], but has never been tested before for proteomic sample preparation. The plate tends to have appealing utilities in the sample preparation for multi-omics studies (e.g., genomics, transcriptomics, proteomics) [55, 56]. Overall, we believe the data present here will make the q96FASP approach much appealing for high throughput quantitative proteome analysis.…”
Section: Discussionmentioning
confidence: 88%